Original paperThe Polish version of Skindex-29: psychometric properties of an instrument to measure quality of life in dermatology - Janowski, Konrad; Steuden, Stanisława; Bereza, Bernarda (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Skin conditions have a negative impact on quality of life and it is necessary to quantify this impact. Skindex-29 is a self-report questionnaire developed to measure dermatology-specific quality of life. Aim: The objective of this study is to adapt this questionnaire to Polish conditions. The adaptation procedure involved the works on the linguistic content of the items and testing psychometric properties of the Polish version of Skindex-29, including item characteristics, factorial structure, aspects of reliability and validity. Material and methods: Two-hundred and ninety patients (63.4% women and 35.2% men) suffering from a range of skin conditions were recruited from several dermatological out-patient and in-patient clinics in Poland. Quality of life was measured using Skindex-29 and appropriate clinical data were collected. Results : The global score of Skindex-29 showed the normal distribution. Cronbach’s  reliability coefficients were found to be high to very high for all Skindex-29 indexes. Factor analysis yielded four factors, in contrast to the original version of the questionnaire, for which a three-factor solution had been reported. Skindex-29 validity was demonstrated by showing the differences in the quality of life scores across different diagnostic categories, and between in-patients and out-patients. Skindex-29 global scores were found to be significantly predicted by the localization of the skin lesions on legs, anogenital areas and palms. Conclusions : The findings of this study support reliability and validity of the Polish version of Skindex-29, but they also raise questions to its three-factor structure.